2008
DOI: 10.1088/0953-8984/20/34/345221
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional mechanism of electrical conductivity in Gd1−xCexBa2Cu3O7−δ

Abstract: Partial substitutions of Pr and Ce are known to suppress the superconducting state in REBa 2 Cu 3 O 7−δ systems. We have substituted Ce for Gd in Gd 1−x Ce x Ba 2 Cu 3 O 7−δ compounds with x = 0.0-0.6 by the standard solid-state reaction technique. X-ray diffraction (XRD) experiments are performed and their results are refined by the Rietveld method. XRD analysis shows a predominantly single-phase perovskite structure with few impurity phases. Our resistivity results show that, by increasing the Ce content, T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Gd has a high magnetic moment and as the Pr concentration is increased in Gd 1−x Pr x Ba 2 Cu 3 O 7−δ compound, T C decreases monotonically, with superconducting state vanishing at a concentration of x = 0.45 [14]. For Gd 1−x Ce x Ba 2 Cu 3 O 7−δ , Mofakham et al observed in the normal state a metal-insulator transition for x ∼ = 0.12 and the disappearance of the superconducting state for x ∼ = 0.6 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Gd has a high magnetic moment and as the Pr concentration is increased in Gd 1−x Pr x Ba 2 Cu 3 O 7−δ compound, T C decreases monotonically, with superconducting state vanishing at a concentration of x = 0.45 [14]. For Gd 1−x Ce x Ba 2 Cu 3 O 7−δ , Mofakham et al observed in the normal state a metal-insulator transition for x ∼ = 0.12 and the disappearance of the superconducting state for x ∼ = 0.6 [15].…”
Section: Introductionmentioning
confidence: 99%